SOSIALISASI IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS MULTIKULTURAL DI KOTA LHOKSEUMAWE - Fina Meilinar; Ifwadi; Muzakkir; Muntadir; Muhammad Iqbal; Rambang Muharramsyah (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
Community service (PKM) activities in the form of Dissemination of the Implementation of Multicultural-Based Character Education in Lhokseumawe City to the Managers of the Cultural Site of Samudra Pasai Kingdom's Royal Tomb Complex and the people reides around the Site in the Gampong Beuringeun, Samudera District, North Aceh Regency, on October 3, 2022. The target participants for this socialization activity were administrators of the Site and the residents around it. The socialization activity was carried out by the PKM Team consisting of lecturers and students of the Social Science Education Study Program, Almuslim University Postgraduate Program as a form of maximizing the meaning of diversity from the level of social status of society and interpreting the importance of historical heritage in the cultural site of Samudra Pasai Kingdom. This socialization activity were expected to increase public awareness and management of the Samudra Pasai Kingdom to improve character in socializing with various levels of social status in society. In addition, this socialization activity is a means of increasing love for historical heritage in the Samudra Pasai Kingdom and continuing to instill the meaning of togetherness and instilling the character of loving the environment by continuing to maintain the cleanliness of historical heritage objects. Thus, it can create a generation that can implement multicultural-based character education.